Heat and Mass Transfer Effects on MHD Nanofluids Past Over an Inclined Plate - Palani, G.; Arutchelvi, A. (International Journal of Engineering and Technology, 2018)
This paper highlights the effects of radiation and MHD nanofluid flowing over a permeable medium that undergoes chemical reaction in first order. The nanoparticles used in the study are copper, aluminium oxide, titanium oxide and silver. The governing partial differential equations are solved by Laplace transform technique. The influences of several values of the physical parameters on velocity,            temperature, concentration profiles are analyzed in an extensive way. The derived findings are depicted in graphs. The numerical      results are found for Skin friction coefficient, Nusselt and Sherwood numbers that are revealed in tabular form.